2018
DOI: 10.1016/j.dib.2018.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of organophosphate esters in sewage sludge: Effects of aerobic/anaerobic treatments and bacterial community compositions

Abstract: This dataset provides detail information on the analytical methods of organophosphate esters (OPEs) in sludge samples, including the sample preparation, ultra-high performance liquid chromatography-tandem mass spectrometric (UPLC-MS/MS) analysis, quality assurance and quality control (QA/QC). The concentration of target OPE compounds in collected samples of four individual treatment was provided, including aerobic composting combined with pig manure (T1), aerobic composting without pig manure (T2), anaerobic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This protein has previously been implicated in diabetes incidence and the control of food intake 25 , 26 , acting via receptors in the hind brain 10 . GDF-15 has also been reported to serve as a useful biomarker for impaired fasting glucose 27 and diabetic kidney disease 28 as well as a number of conditions including cardiovascular disease 29 , 30 GDF15 is strongly elevated following metformin exposure, due to release from the gut 31 . Of note, we did not show any attenuation of the GDF15 signal with progression when adjusting for whether the patients were treated with metformin at the time of blood sampling.…”
Section: Discussionmentioning
confidence: 99%
“…This protein has previously been implicated in diabetes incidence and the control of food intake 25 , 26 , acting via receptors in the hind brain 10 . GDF-15 has also been reported to serve as a useful biomarker for impaired fasting glucose 27 and diabetic kidney disease 28 as well as a number of conditions including cardiovascular disease 29 , 30 GDF15 is strongly elevated following metformin exposure, due to release from the gut 31 . Of note, we did not show any attenuation of the GDF15 signal with progression when adjusting for whether the patients were treated with metformin at the time of blood sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Male subjects were more abundant in the cohorts (>55%), and the average age ranged from 61-67 years with a BMI of 30-32 kg/m 2 . Glycated haemoglobin (HbA1c) levels were on average lowest in DCS (median[Q25-Q75]: 47.08 [42][43][44][45][46][47][48][49][50] mmol/mol), followed by GoDARTS (55.54 [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] mmol/mol) and ANDIS (60.06[46.0-68.0]). The time from diagnosis to sampling time ranged from 0 to 2.63 years.…”
Section: Cohort Characteristics and Modelling Of Glycaemic Deteriorationmentioning
confidence: 99%
“…This protein has previously been implicated in diabetes incidence and the control of food intake 43,44 , acting via receptors in the hind brain. 28 GDF-15 has also been reported to serve as a useful biomarker for impaired fasting glucose 45 and diabetic kidney disease 46 as well as a number of conditions including cardiovascular disease 47,48 GDF15 is strongly elevated following metformin exposure, due to release from the gut. 49 Of note, we did not show any attenuation of the GDF15 signal with progression when adjusting for whether the patients were treated with metformin at the time of blood sampling.…”
Section: Proteins and Glycaemic Deteriorationmentioning
confidence: 99%
“…OP triesters were not completely removed in WWTPs following advanced oxidation processes (Cristale et al, 2016;Liang et al, 2016). Low removal rates of OP triesters also were reported following aerobic composting of sewage sludge (Pang et al, 2018). Thus far, only a few studies have reported on the occurrence of OP triesters and diesters in sewage sludge from the US (Kim et al, 2017), European countries (Celano et al, 2014;Marklund et al, 2005), and China (Fu et al, 2017;Gao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%